Effects of different mulching practices on soil properties and soil microbial communities in tomato production - Li, Xiaoxia; Cao, Jinjun; Li, Dan; Jin, Kunpeng; Liu, Yongzhong; Li, Wanxing (Frontiers in Microbiology, 2026)
IntroductionAgricultural mulches are commonly used for their benefits, however, the mechanisms by which they affect microbial communities to mediate soil properties that influence tomato growth remain unclear.MethodsA three-year experiment was conducted comparing four treatments: plastic film mulching alone (SBF), straw mulching alone (SM), film-straw dual mulching (SBFSF), and no mulching (CK). Their effects on soil properties, microbial communities, and tomato growth were systematically evaluated.ResultsAll mulching treatments significantly increased tomato yield, with SBF, SM, and SBFSF demonstrating improvement of 32.87%, 22.17%, and 50.17%, respectively. SBFSF exhibited the greatest dry matter weight (shoot plus root), root length, and root surface area 40 days post-transplanting, and it showed the strongest effect on soil moisture and thermoregulation. SM and SBFSF significantly increased soil organic carbon (SOC: +5.92%, +4.04%), total nitrogen (TN: +6.34%, +4.46%), available potassium (AK: +18.15%, +10.91%), and available phosphorus (AP: +2.60%, +2.15%). SBFSF significantly reduced the diversity of soil bacteria and fungi, howerer, it selectively increased the relative abundances of plant growth-promoting rhizobacteria and functional microorganisms involved in carbon-nitrogen cycling, such as the bacterial phylum Firmicutes(+125.18% to +193.55%), genera Lysobacter (+49.19% to +186.62%) and Bacillus (+168.56% to +273.00%), and fungal phyla Ascomycota (+7.99% to +8.19%) and Mortierellomycota (+11.05% to +98.71%), including the genus Trichocladium (+30.43% to +269.95%). In contrast, SM and SBF led to an increase in the abundance of pathogenic fungi (Fusarium, Cladosporium, Alternaria, and Cephaliophora), elucidating their inferior yield performance compared to SBFSF.DiscussionPartial least squares path modeling (PLS-PM) analysis indicated that mulching practices directly and positively influenced the soil bacterial and fungal community composition and negatively affected soil fungal community diversity, which indirectly effecting tomato growth by modulating soil properties. These results provide a scientific foundation for improving mulching, and sustainable agricultural practices.